Food Safety and Civil Liability of the Enterprise from the Comparative Law Perspective - Cham, Nguyen Thi Phuong (VNU Journal of Science: Legal Studies; Vol 35 No 2, 2019)
Civil liability, as a method to directly protect the rights and legitimate interests of consumers, plays an important role in improving the legal provisions on food safety. However, the legal issues related to civil liability in general and, especially, civil liability in the field of food safety, remain highly controversial by the diversity of relationships among the subjects in the process of production, circulation and consumption. The paper focuses on: (1) Clarifying theoretical and practical provisions applied from the comparative law perspective, thus pointing out the problems that exist in the legal system in general and in the Vietnamese legal system in particular, on civil liability in the field of food safety; (2) Suggesting some comprehensive solutions for the purpose of introducing civil liability mechanisms, such as protecting the rights and interests of consumers in a practical and effective way; preventing violations of business in the context of science and technology development; and risk dispersion based on the theory of the balance of interests of civil legal subjects. Keywords: Food safety, civil liability, tort law, product liability. References: [1] Xiang Li, Jigang Jin, Concise Chinese Tort Laws, Springer-Verlag Berlin Heidelberg, 2014. [2] Niwata Noriaki, Sự cố thực phẩm và vấn đề người tiêu dùng, Nghiên cứu Thương mại Mitsuda 27 (3). [3] Tạp chí án lệ số 307 (1974) 87-101. [4] Nakamura Hiroshi, Vi phạm hợp đồng và phương thức bảo vệ quyền (2), Tạp chí Đại học Doshisha 32 (3) (1980). [5] Tạp chí Án lệ số 1109; Tạp chí thời báo án lệ số 1805. [6] Nozawa, Nghiên cứu pháp luật so sánh trách nhiệm đảm bảo khuyết tật Masamishi (6) - Nhật bản, Pháp. EU, Tạp chí Luật học Rikkyo 91 (2015). [7] Suzuki Miyako “Hạn bảo quản và trách nhiệm đảm bảo khuyết tật trong luật Đức” Tuyển tập luận văn đại học ngoại ngữ Tokyo, 91 (2015). [8] Felix Maultzsch, Hướng phát triển mới về trách nhiệm đảm bảo khuyết tật của người bán trong pháp luật Đức và Liên minh Châu Âu, Tạp chí nghiên cứu pháp luật chính sách 82 (2). [9] Katsuhiko Akabori, Luật trách nhiệm sản phẩm và quản lí rủi ro doanh nghiệp, Tạp chí luật học Học viện Kobe, 38 (3,4) (2009) 35. [10] Uchida, Bảo hiểm trách nhiệm bồi thường thiệt hại và sự tham gia của doanh nghiệp đến đâu?, Tạp chí thứ 6, 26 (7) (2018).